ROLE STRESSOR, SELF-COMPASSION AND HEALTHY LIFESTYLE ON AUDITOR PERFORMANCE: CASE OF BALI PROVINCE - Luh Komang Merawati (Journal of International Conference Proceedings (JICP), 2019)
This study aims to determine the effect of role stressors, self-compassion and healthy lifestyle on the performance of government auditors in BPKP and BPK RI Representative of Bali Province in Denpasar. Role stressor dimensions include role ambiguity, role overload and role conflict. Data was obtained by distributing questionnaires and analyzed using multiple linear regression. The results indicate that role ambiguity and role overload negatively affect auditor performance while role conflict, self-compassion and healthy lifestyle do not affect auditor performance.